2019
DOI: 10.1111/bjd.18331
|View full text |Cite
|
Sign up to set email alerts
|

Sustained efficacy of secukinumab in patients with moderate‐to‐severe palmoplantar psoriasis: 2·5‐year results from GESTURE , a randomized, double‐blind, placebo‐controlled trial

Abstract: Summary Background Secukinumab has shown sustained efficacy and safety in several manifestations of psoriasis. Objectives GESTURE investigated the long‐term (2·5‐year) safety and efficacy of 150 mg and 300 mg subcutaneous secukinumab in 205 patients with moderate‐to‐severe palmoplantar psoriasis. Methods GESTURE was a randomized, double‐blind, placebo‐controlled, multicentre, phase IIIb trial conducted across 15 countries. The study was 140 weeks long and consisted of four periods: screening (up to 4 weeks), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…In particular 90% reduction in PASI (PASI90), from baseline PASI score, and 100% reduction in PASI (PASI100) were recorded, respectively, in 79% and 44.3% of patients after 16 weeks of therapy; in both cases these rates were significantly higher compared to ustekinumab ( P < .001) 15 . Several other phase III trials demonstrated its long‐lasting efficacy in many different clinical manifestations of psoriasis, including nails, scalp, palmoplantar, and joints 16‐18 …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular 90% reduction in PASI (PASI90), from baseline PASI score, and 100% reduction in PASI (PASI100) were recorded, respectively, in 79% and 44.3% of patients after 16 weeks of therapy; in both cases these rates were significantly higher compared to ustekinumab ( P < .001) 15 . Several other phase III trials demonstrated its long‐lasting efficacy in many different clinical manifestations of psoriasis, including nails, scalp, palmoplantar, and joints 16‐18 …”
Section: Introductionmentioning
confidence: 96%
“…15 Several other phase III trials demonstrated its long-lasting efficacy in many different clinical manifestations of psoriasis, including nails, scalp, palmoplantar, and joints. [16][17][18] Although data regarding the long-term sustained efficacy and safety of secukinumab are available from randomized clinical trials, 19 there is a need to increase real-world studies on this topic. Indeed, real-world patients with psoriasis are very different from those enrolled in clinical trials, which can strongly influence biologic treatment clinical outcomes as well as the course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Biologics inhibiting the T-helper (Th)-17 pathway have been approved for plaque psoriasis, psoriatic arthritis, and ankylosing spondylitis, 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 and are currently under investigation for rheumatoid arthritis. 9 This group of biologics include IL-17 inhibitors (secukinumab, ixekizumab, brodalumab), and IL-12/23 inhibitors (IL-12/23p40 (ustekinumab), IL-23p19 (guselkumab)).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, palmoplantar psoriasis is also frequently resistant to treatment, making it quite a therapeutic challenge [2]. Biologic therapies, such as secukinumab, an anti-interleukin (IL) 17A monoclonal antibody, have been highly effective in the management of resistant palmoplantar psoriasis, as shown in the 2PRECISE randomized controlled trial [3] and GESTURE trial [4]. Risankizumab, another biologic therapy, is a humanized immunoglobulin (Ig) G1 monoclonal antibody that targets the p19 subunit of IL-23 [5].…”
Section: Introductionmentioning
confidence: 99%